Contemporary Europe (Palgrave foundations, 2012)
"This fully revised third edition provides a wide-ranging introduction to political, economic and social life across the whole continent. Ideal for students new to the subject, this popular text stimulates fresh thinking on issues and debates"--Provided by publisher.